2022
DOI: 10.1101/2022.09.29.510029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain-wide associations between white matter and age highlight the role of fornix microstructure in brain ageing

Abstract: Identifying white matter (WM) microstructure parameters that reflect the underlying biology of the brain will advance our understanding of ageing and brain health. In this extensive comparison of brain age predictions and age-associations of WM features from different diffusion approaches, we analysed UK Biobank diffusion Magnetic Resonance Imaging (dMRI) data across midlife and older age (N = 35,749, 44.6 to 82.8 years of age). Conventional and advanced dMRI approaches were consistent in predicting brain age;… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 115 publications
6
31
0
Order By: Relevance
“…Additionally, there are differences between models trained on voxel-level compared to region-averaged data. Deep learning models using voxel-level data reach age predictions errors as low as MAE = 2.14 years in midlife to late adulthood (Peng et al, 2021) or MAE = 3.90 years across the lifespan (Leonardsen et al, 2022) while explaining large proportions of variance in age (R 2 > 0.90), whereas models trained on regional and global average measures predict age usually with larger error, MAE > 3.6 years, and/or lower variances explained R 2 < 0.75 (Beck et al, 2021, 2022; de Lange et al, 2020a, 2020b; Korbmacher et al, 2022; Rokicki et al, 2021). However, Niu et al (2019) showed that with different shallow and deep machine learning algorithms (ridge regression, support vector regressor, Gaussian process regressor, deep neural networks) high prediction accuracies (R 2 > 0.75, MAE < 1.43) could be reached when using multimodal regional average data using a young sample with narrow age range.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, there are differences between models trained on voxel-level compared to region-averaged data. Deep learning models using voxel-level data reach age predictions errors as low as MAE = 2.14 years in midlife to late adulthood (Peng et al, 2021) or MAE = 3.90 years across the lifespan (Leonardsen et al, 2022) while explaining large proportions of variance in age (R 2 > 0.90), whereas models trained on regional and global average measures predict age usually with larger error, MAE > 3.6 years, and/or lower variances explained R 2 < 0.75 (Beck et al, 2021, 2022; de Lange et al, 2020a, 2020b; Korbmacher et al, 2022; Rokicki et al, 2021). However, Niu et al (2019) showed that with different shallow and deep machine learning algorithms (ridge regression, support vector regressor, Gaussian process regressor, deep neural networks) high prediction accuracies (R 2 > 0.75, MAE < 1.43) could be reached when using multimodal regional average data using a young sample with narrow age range.…”
Section: Discussionmentioning
confidence: 99%
“…Brain age was predicted using the XGBoost algorithm implemented in Python (v3.7.1), being a highly effective algorithm for tabular data (Chen & Guestrin, 2016). From the total included sample (N = 35,749), we used 10% (N = 3,575) for hyperparameter tuning on a data set containing data from all diffusion approaches (i.e., full multimodal data with 1,932 features/parameters) using 5-fold cross-validation (after estimating an optimal hyperparameter tuning set size (Korbmacher et al, 2022)). The considered hyperparameters for the randomized grid search were learning rate with a range of 0.01 to 0.3 and steps of 0.05, maximum layers/depth with a range of 3 to 6 and steps of 1, and number of trees with a range of 100 to 1000 and steps of 50.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations